Unilateral isolated incompletely duplicated ureter - Yuganti P Vaidya; Jwalant E Waghmare; Aaditya M Tarnekar; Moreshwar R Shende (Wolters Kluwer Medknow Publications, 2014)
The aim of this study was to report a congenital anomaly in a cadaveric dissection. During routine undergraduate dissection in a middle-aged male cadaver, we found that on the left side, there was a presence of an incompletely duplicated ureter. On the right side the ureter was single in its whole extent. No other congenital anomaly was found to be associated with this. The two limbs of the left ureter joined at about a distance of 5 cm from the bladder wall. A duplicated ureter is commonly found in association with other congenital anomalies and defects. The present case report describes a rare case of an isolated duplicated ureter with a normal kidney, urinary bladder, and renal vessels. This case report adds on to the literature and will be helpful and interesting for the surgeons. The possible embryological reasons for the formation of a duplicated ureter will be discussed.